2020
DOI: 10.30699/ijp.2020.127312.2387
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of patient-collected and lab technician-collected nasopharyngeal and oropharyngeal swabs for detection of COVID-19 by RT-PCR

Abstract: Scan to discover online Background & Objective: A simple approach to prevent close contact in healthcare settings during the COVID-19 outbreak is to train patients to collect their own nasopharyngeal and oropharyngeal swabs and deliver them to medical laboratories to have them processed. The aim of our study was to compare lab technician-with patientcollected oropharyngeal and nasopharyngeal samples for detection of the coronavirus disease 2019 (COVID 19) using rapid real-time polymerase chain reaction (rRT-PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…The 3 other studies ( 55 , 56 , 58 ) in this meta-analysis did not specify self-collection versus health care worker collection. There was one study ( 60 ) that compared self-collected versus lab technician-collected OP swabs and found that only 14/24 total positives were detected by self-collection versus 22/24 total positives for lab technician collected. This study was excluded from this meta-analysis, however, as the pairing of OP swabs to NP swabs was unclear.…”
Section: Resultsmentioning
confidence: 99%
“…The 3 other studies ( 55 , 56 , 58 ) in this meta-analysis did not specify self-collection versus health care worker collection. There was one study ( 60 ) that compared self-collected versus lab technician-collected OP swabs and found that only 14/24 total positives were detected by self-collection versus 22/24 total positives for lab technician collected. This study was excluded from this meta-analysis, however, as the pairing of OP swabs to NP swabs was unclear.…”
Section: Resultsmentioning
confidence: 99%
“…The 3 other studies (55, 56, 58) in this meta-analysis did not specify self-vs. healthcare-worker collection. There was one study (60) that compared self-versus lab-technician collected OP swabs and found that only 14/24 total positives were detected by self-collection versus 22/24 total positives for lab-technician-collected. This study was excluded from this meta-analysis, however, as the pairing of OP swabs to NP swabs was unclear.…”
Section: Resultsmentioning
confidence: 99%
“…These findings differed from a study by Abdollahi et al . [ 24 ] with a sensitivity of less than 70% and a specificity of less than 95%, in which, it was concluded that samples collected by professionals were more reliable than self-collected samples. The study by Abdollahi, however, was carried out on a small sample size of 50 patients, which might be a factor in the result realized, also, the median age of participants was 56 years compared to our study which had a median age of 35 years.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Abdollahi, however, was carried out on a small sample size of 50 patients, which might be a factor in the result realized, also, the median age of participants was 56 years compared to our study which had a median age of 35 years. Another factor that could be responsible for such a contradiction is that 9 out of 11 patients who reported having underlying conditions according to Abdollahi, [ 24 ] have severe medical conditions. They concluded that self-collection is not recommended for patients with severe medical conditions.…”
Section: Discussionmentioning
confidence: 99%